Tantangan Penegakan Hukum Perdata di Era Digital - Santiana Siboro; Sri Hadiningrum (Universitas 17 Agustus 1945 Semarang, 2024)
The development of science and technology has positive and negative impacts on human life. Likewise with cyberspace, one of the advances in technology, of course it is a reality that is faced with a legal metanarrative. Overcoming the ineffectiveness of legal metanarratives in addressing cyber challenges requires an innovative and comprehensive approach. Currently the world is facing changes in the industrial world which can be called the Industrial Revolution 4.0 which has a major impact on industrial life, especially in the form of rapid technological developments. The rapid development of technology has given birth to a new concept of